Clinical outcome of cystic fibrosis patients colonized by Scedosporium species following lung transplantation: A single‐center 15‐year experience. Issue 5 (1st August 2017) - Parize, Perrine; Boussaud, Veronique; Poinsignon, Vianney; Sitterlé, Emilie; Botterel, Francoise; Lefeuvre, Sandrine; Guillemain, Romain; Dannaoui, Eric; Billaud, Eliane M.
Abstract: Background: Fungi of the genus Scedosporium are emerging pathogens responsible for severe infections in lung transplant recipients. These infections are associated with poor prognosis and some centers consider now Scedosporium species colonization as a contraindication to lung transplantation (LT) even though no published evidence demonstrates that Scedosporium species colonization is associated with higher morbidity or mortality after LT. Methods: Here, we aim to describe characteristics and outcome of cystic fibrosis (CF) lung transplant recipients colonized with Scedosporium species in a single center over a 15‐year period. Results: During the study period, 14 patients had scedosporial colonization reported. Only one patient, colonized before transplantation by Lomentospora prolificans, developed scedosporial disease. Among the eight patients colonized before transplantation by Scedosporium apiospermum complex, the median survival was 1.92 year (range 0.21‐12.5). All these patients except one became free of fungal colonization after transplantation with antifungal prophylaxis including voriconazole or posaconazole. For the five patients colonized after LT, including two with L. prolificans, the median survival was 1.75 years (range 0.1‐13); three of them are still alive. Conclusions: It appears to us that scedosporial colonization may not be a contraindication for LT in CF patients, as long as S. apiospermum complex is involved and a life‐long azole prophylaxis prescribed.